Local electronic structure investigation of the sol-gel processed calcium hydroxide material - 씽 지텐드라; 김소희; 임원철; 원성옥; 채근화 (2018 VBRI Press, 2018)
In the present work, we have reported the synthesis of calcium hydroxide from calcium nitrate. Synthesized nanoparticles were characterized using X-ray diffraction, scanning electron micrographs, and near edge X-ray absorption fine structure measurements. Synthesized nanoparticles exhibit tetragonal phase with space group P3m1. These nanoparticles exhibit almost spherical shape. Particle size of these nanoparticles are 55 nm and 69 nm for two different treatment of precursor. Microscopic studies shows that size distribution is affected by the change of thermal history. Local electronic structure measured at Ca (L- & K-) and O K-edges exhibit presence of spectral features that are characteristics of calcium hydroxide. Moreover, strength and magnitude of crystal field parameter is unaffected by thermal treatment utilized for synthesis of these materials.